2015
DOI: 10.1007/s12529-015-9487-x
|View full text |Cite
|
Sign up to set email alerts
|

Larger and More Prominent Graphic Health Warnings on Plain-Packaged Tobacco Products and Avoidant Responses in Current Smokers: a Qualitative Study

Abstract: Consistent with theories of illness perceptions and coping, current findings indicate that the larger, prominent graphic health warnings on plain-packaged tobacco products had pervasive effects on threat perceptions and subsequent behavioural responses. While some of the reported responses were adaptive (e.g. attempts to quit), others were maladaptive (e.g. avoiding the warnings).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…As already hinted at, techniques of avoidance were common throughout the three fieldsites with graphic warning labels in place, a phenomenon that has also been reported in a recent qualitative study on Australian smokers' responses to plain packaging (see Hardcastle et al, 2015). In Vancouver and Canberra, a minority of participants decanted cigarettes to other containers or certain packets were exchanged for ones with less threatening warnings (6 of 60 in Vancouver, 9 of 70 in Canberra).…”
Section: Techniques Of Avoidance Refusals Of Engagementsupporting
confidence: 54%
“…As already hinted at, techniques of avoidance were common throughout the three fieldsites with graphic warning labels in place, a phenomenon that has also been reported in a recent qualitative study on Australian smokers' responses to plain packaging (see Hardcastle et al, 2015). In Vancouver and Canberra, a minority of participants decanted cigarettes to other containers or certain packets were exchanged for ones with less threatening warnings (6 of 60 in Vancouver, 9 of 70 in Canberra).…”
Section: Techniques Of Avoidance Refusals Of Engagementsupporting
confidence: 54%
“…However, diagnosis with coronary artery disease was not related to attitudes or intentions to participate in self-management behaviors. To speculate, it may be that such representations may lead to maladaptive coping behaviors such as avoidance or denial, a finding that has been identified in previous research [68].…”
Section: Discussionmentioning
confidence: 79%
“…However, smokers are not necessarily exposed to warnings when they take a cigarette, including in markets with plain packaging, one of the core aims of which is to prevent pack design from detracting from the warnings. In Australia, for instance, there is evidence that some smokers use cases, reuse fully-branded packs, or cover or conceal packs (Wakefield et al 2015;Hardcastle et al 2016;Yong et al 2016), and eye-tracking research has shown regular smokers to fixate on the branding rather than the warning on plain packs (Maynard et al 2014). The general view in this study was that warnings on each cigarette stick would make avoidant behavior more difficult as smokers typically see a cigarette when taking it from a pack, lighting it, leaving it in an ashtray, and smoking it.…”
Section: Discussionmentioning
confidence: 99%